Lactating performance, water and feed consumption of rabbit does reared under a Mediterranean summer circadian cycle of temperature v. comfort temperature conditions. (16th January 2015) - Bakr, M. H.; Tusell, L.; Rafel, O.; Terré, M.; Sánchez, J. P.; Piles, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The general aim of this research was to study the effect of high ambient temperature on the performance of does during lactation, specifically the following factors: average daily feed (ADFI) and water (ADWI) intakes, daily milk yield (DMY); milk composition: dry matter (DM), CP and gross energy (GE); doe BW (DW); individual kit weaning weight (IWW) and litter survival rate during lactation (SR). The study was undertaken comparing the performance of two groups of contemporary does reared under the same management, feeding regime and environmental conditions, except the environmental temperature and humidity. A total of 80 females were randomly allocated, at 60 days of age, into two identical and continuous rooms. In one room, the temperature was maintained permanently within the thermo-neutral zone (between 18°C to 22°C); thus, environmental conditions in this room were considered as comfort conditions. In the second room, the environmental temperature pattern simulated the daily temperature cycles that were characteristic of the summer in Mediterranean countries (24°C at 0800 h, increasing up to 29°C until 1100 h; maintenance at 29°C to 31°C for 4 h and decreasing to about 24°C to 26°C around 1700 h until 0800 h of the following day), which were considered as thermal stress conditions. Females followed a semi-intensive reproductive rhythm, first artificial insemination at 4.5 months of age, with subsequent 42-day reproductive cycles. Traits were recorded from a total of 138 lactations. Does were controlled up to the 5th lactation. Data were analyzed using linear and linear mixed models. High ambient temperature led to a lower ADFI (−9.4%), DW (−6.2%) and IWW (−8%), but it did not affect ADWI. No significant difference was found either for DMY, milk composition (DM, CP and GE) and SR during the lactation period. Heat stress was moderate, and does were able to adapt to it behaviorally by decreasing feed intake (to reduce heat production), but also live weight, allowing them to preserve milk yield and composition for assuring litter survival. On the other hand, water consumption could not be the main animal mechanism to overcome heat stress.